A critical view of critical velocity testing to predict performance - Jolly, S. (Journal of Sports Sciences, 2013)
The paper is a short and critical view about critical velocity testing to predict performance. It is concluded that it is not clear how the use of repeated performance tests to predict other performances, provides an advantage over a single-criterion performance test.